Análisis y Evaluación Económica y Financiera de la Constructora COYANTZA, Cía. Ltda., del Cantón Yanzatza, Periodo 2013 - 2014 - Sarango Campoverde, Viviana Elizabeth (2016)
This thesis entitled "Economic and Financial Analysis and Evaluation of the Construction Co. COYANTZA. Ltda., Canton Yanzatza, Period 2013-2014 "was conducted in compliance prior to obtaining the title of Engineer in Accounting and Auditing, Certified Public Accountant Auditor, also for the purpose requirement to disclose the financial-economic development of the company in the periods indicated and then to a good and proper decision-making with the proper functioning of the same. The methodology applied for execution was to gather credible and reliable information from the authorities of the company, in order to apply the procedures of financial analysis and determine its liquidity, indebtedness, profitability and activity possessed in years evaluated. Then he was made based on the objectives for which they proceeded to apply and interpret financial indicators of liquidity, activity, indebtedness and profitability, and those established by the appropriate regulating body, where critical points were established for decision making , determining that the company has a high percentage of debt in a given period. evaluation of the financial structure was performed in order to examine each of the accounts included, managing to maintain an acceptable level 5 in the financial management of the company; therefore it was important to the analysis of economic performance and operational to know how efficient the company. Finally an analysis report and financial evaluation, which contains the conclusions and recommendations that will serve as financial guidance to shareholders for better decision-making in the company is made.